2021
DOI: 10.26636/jtit.2021.148020
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis of Filtered OFDM Based Downlink and Uplink NOMA System over Nakagami-m Fading Channel

Abstract: Efficient consumption of available resources and fulfillment of increasing demands are the two main challenges which are addressed by exploring advanced multiple access schemes along with efficient modulation techniques. To this end, non-orthogonal multiple access (NOMA) is discussed as a promising scheme for future 5G traffic. NOMA enables the users to share same resource block, permitting certain level of interference. In this paper, we propose filtered OFDM (F-OFDM) as a transmission waveform for NOMA syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…5 (a-b) over AWGN and Rayleigh fading channels respectively. As compared with the results get in [14], the full-band-based filtering scenario provides almost the same error floor with a benefit of approximately 11dB SNR, while the subband-based filtering scenario achieves almost the same error floor with a benefit of approximately 17dB SNR. The BER better performance of the proposed system as compared with ref [14] is due to SINR gain through employing the 5G frame structure.…”
Section: Resultsmentioning
confidence: 63%
See 3 more Smart Citations
“…5 (a-b) over AWGN and Rayleigh fading channels respectively. As compared with the results get in [14], the full-band-based filtering scenario provides almost the same error floor with a benefit of approximately 11dB SNR, while the subband-based filtering scenario achieves almost the same error floor with a benefit of approximately 17dB SNR. The BER better performance of the proposed system as compared with ref [14] is due to SINR gain through employing the 5G frame structure.…”
Section: Resultsmentioning
confidence: 63%
“…Table .1 displays the simulation parameters of the proposed system considering two scenarios. Since the work in [14] considered combining NOMA technique and fullband based F-OFDM, equivalent parameters are considered in scenario-I for performance comparison. As in [14], Binary Phase Shift Keying (BPSK) modulation is used for FU while Quadrature Phase Shift Keying (QPSK) is used for NU due to channel conditions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the various technical aspects of NOMA have been widely discussed. In [8] and [9], the authors have analyzed different modulation techniques for improving the performance of NOMA system. In [10], the authors have shown that NOMA has superior energy efficiency performance in comparison with conventional orthogonal multiple access.…”
Section: Introductionmentioning
confidence: 99%